Light microscopic description of the effects of laser phototherapy on bone defects grafted with mineral trioxide aggregate, bone morphogenetic proteins, and guided bone regeneration in a rodent model - Pinheiro, Antonio L. B.; Soares, Luiz G. P.; Aciole, Gilberth T. S.; Correia, Neandder A.; Barbosa, Artur F. S.; Ramalho, Luciana M. P.; dos Santos, Jean N. (Journal of biomedical materials research. Part A, 2011)
We carried out a histological analysis on bone defects grafted with mineral trioxide aggregate (MTA) treated or not with laser, bone morphogenetic protein (BMP), and guided bone regeneration (GBR). Benefits of the use of MTA, laser, BMPs, and GBR on bone repair are well known, but there is no report on their association with laser light. Ninety rats were divided into 10 groups each subdivided into 3. Defects on G II and I were filled with the blood clot. G II was further irradiated with LED. G III and IV were filled with MTA; G IV was further irradiated with laser. G V and VI, the defects filled with MTA and covered with a membrane (GBR). G VI was further irradiated with laser. G VII and VIII, BMPs were added to the MTA and group VIII further irradiated with laser. G IX and X, the MTA + BMP graft was covered with a membrane (GBR). G X was further irradiated with laser. Laser light (λ = 850 nm, 150 mW, 4 J/cm2) was applied over the defect at 48‐h intervals and repeated for 15 days. Specimens were processed, cut and stained with H&E and Sirius red and underwent histological analysis. Subjects on group X were irradiated. The results showed different tissue response on all groups during the experimental time. Major changes were seen on irradiated subjects and included marked deposition of new bone in advanced maturation. It is concluded that near infrared laser phototherapy improved the results of the use of the MTA on bone defects. © 2011 Wiley Periodicals, Inc. J Biomed Mater Res Part A:, 2011.